E-SPORT ARENA RESPON DARI KEBUTUHAN KAUM MILENIAL - Indro Indro; Andi Surya Kurnia (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
E-Sport in South Korea has become one of the country's big income. E-Sport has a considerable influence on the country. Therefore E-Sport is questionable from local to international. The facilities needed for E-Sport also really need to be related to training places for people who want to become E-Sports athletes in order to be able to participate in international competitions. In some developed countries, the video game again recommends a vehicle to spend free time being asked to be a profession with income that is quite convincing. This profession is an Athlete professional in this case who is an expert in playing video games or who has been widely known as e-Athlete. If you have been given the title of the athlete, things that must be categorized in sports are given the name E-Sport. In Indonesia itself, with the recognition that the Indonesia E-Sport Association (IeSPA) as an organization that respects Kemenpora is also a bright spot for the development of sports in our country. Although E-Sport shows don't seem difficult to do just because a computer with high specifications is needed, however, it is necessary to implement it requiring a place with a certain arrangement of spaces. So that athletes who will compete can simplify the game. Therefore a place that is specifically designed to carry out E-Sport events is needed.AbstrakE-Sport seperti di Korea Selatan menjadi salah satu pendapatan yang cukup besar bagi negara itu. E-Sport memiliki dampak yang cukup besar bagi sebuah negara. Karenanya E-Sport dipertandingkan dari lokal sampai ke internasional. Kebutuhan sarana untuk E-Sport juga sangat perlu apalagi dengan adanya tempat pelatihan bagi masyarakat yang ingin menjadi atlet E-Sport sehingga dapat mengikuti kompetisi di dunia Internasional. Di beberapa negara maju video game bukanlah lagi sebuah wahana untuk menghabiskan waktu luang melainkan menjadi sebuah profesi dengan pendapatan yang cukup meyakinkan. Profesi tersebut dengan adalah menjadi atlit professional dalam kasus ini yang ahli dalam bermain video game atau yang sudah banyak dikenal orang dengan sebutan e-Atlit. Di Indonesia sendiri, dengan diakuinya Indonesia E-Sport Association (IeSPA) sebagai organisasi yang diakui Kemenpora turut menjadi titik terang perkembangan olahraga ini di negeri kita. Untuk bangunan E-Sport di Indonesia sudah ada sejak dulu karenanya dalam perancangan akan memakai metode preseden untuk mengambil apa aja yang menjadi sebuah ciri bangunan E-Sport. Keberadaan bangunan E-Sport di Jakarta banyak terletak di Jakarta Barat terutama kawasan Palmerah, jadinya lokasi tapak diperkirakan berada di Palmerah.